ANALISIS DIFERENSIASI KARYA PADA KEMAMPUAN LITERASI SAINTEK MAHASISWA KEPENDIDIKAN UNIVERSITAS PGRI SEMARANG - Reffiane, Fine; Huda, Choirul; Mudzanatun, Mudzanatun; Agustini, Ferina (Universitas Muria Kudus, 2024)
This research aims to analyze the differentiation of works on the Scientific and Technological Literacy Abilities of PGRI Semarang University Education Students. This is because the diversity of student work is a gift in learning. Existing works must be empowered and their creativity enhanced. Differentiation of work is a form of student work that should be appreciated. The research method used in this research is a qualitative analysis method. The subjects of this research were education students at PGRI University Semarang. The research was conducted for 1 semester in two fields of study, namely the Professional Teacher Education study program and the Primary School Teacher Education study program. There are 4 success indicators used to determine the success of research. namely product quality, product reliability, team performance, product design. From these indicators, the following results were obtained: (1) product quality received a very good qualification, namely 43.56%, (2) product reliability received a very good qualification, namely 48.55%, (3) product performance received a very good qualification of 49.63%, (4) product design received very good qualifications of 37.07%. The high qualification indicators of research results can be used as a reference for the success of carrying out research activities.